2023
DOI: 10.21203/rs.3.rs-3010524/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Level of noise-induced hearing loss and associated factors among workers in Bishoftu central air base of Ethiopia

Ashenafi Hailu,
Birhanu Zeleke,
Zeberihe Ermias
et al.

Abstract: Background Excessive occupational exposure to noise results in occupational hearing loss was considered a major public health problem. Since the expansion of the aviation industry and its exposure to the intensity of noise level was simultaneously high. Objective This study aims to assess the level of noise-induced hearing loss and associated factors among workers in the Bishoftu central air base in Ethiopia. Methods Institutional-based cross-sectional study was conducted among 260 central air base workers thr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The sample size was determined using a single population proportion formula considering the p prevalence of NIHL 22% among Akaki basic metal industry workers 16 . A 95% confidence interval and a 5% margin of error were used to calculate the sample size.…”
Section: Sample Size Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size was determined using a single population proportion formula considering the p prevalence of NIHL 22% among Akaki basic metal industry workers 16 . A 95% confidence interval and a 5% margin of error were used to calculate the sample size.…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…Moreover, several studies have reported that the predictive factors related to NIHL were being male sex, higher age, duration of exposure or service year, noise intensity level, exposure to an explosion, vibration, smoking, ceruminous occlusion of the external auditory canal, and utilization of hearing protective devices as preventive factors [14][15][16] .…”
mentioning
confidence: 99%
See 1 more Smart Citation